The effect of alkaline heat treatment on titanium - Kartikasari, Nadia; Andaru, Salsabilla Eliya; Shallomitha, Aginta Gracia; Sitalaksmi, Ratri Maya (Indonesian Journal of Dental Medicine, 2024)
Background: In recent years, advancements in implant surface modification have garnered considerable interest within the field of biomedical engineering, particularly in dental and orthopaedic implants. High-rise surface modifications demonstrate significant promise in enhancing osseointegration, improving cellular adhesion, and accelerating the healing process. One notable technique, alkaline-heat treatment (AHT), has shown potential for enhancing both the mechanical and biological performance of titanium implants. Purpose: The objective of this review is to provide a comprehensive overview of the properties and outcomes associated with alkaline-heat treatment for titanium implants, with a specific focus on the potential benefits for dental applications. Review: Based on an analysis of 13 review articles, titanium implants treated with alkaline heat exhibit distinctive properties that enhance their biological efficacy. These include superior osseointegration, improved immunological responses, and heightened antibacterial potential. Conclusion: Alkaline-heat treatment significantly enhances titanium implants by creating a nano topography that fosters osseointegration, bolsters immune responses, and exhibits antibacterial effects. These characteristics position AHT as a promising solution for preventing peri-implantitis and facilitating implant healing.